2011
DOI: 10.1002/hipo.20913
|View full text |Cite
|
Sign up to set email alerts
|

A role for the CAMKK pathway in visual object recognition memory

Abstract: The role of the CAMKK pathway in object recognition memory was investigated. Rats' performance in a preferential object recognition test was examined after local infusion into the perirhinal cortex of the CAMKK inhibitor STO‐609. STO‐609 infused either before or immediately after acquisition impaired memory tested after a 24 h but not a 20‐min delay. Memory was not impaired when STO‐609 was infused 20 min after acquisition. The expression of a downstream reaction product of CAMKK was measured by immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Previous studies that compared gene expression in perirhinal cortices of rats exposed to either novel or familiar 3D objects or 2D images found increases in protein levels upon neuronal activation in response to the novel compared to the familiar stimulus [10], [11], [12], [13], [14], [37], [38]. Intriguingly, when the transcriptomes of groups Novel and Familiar were compared, a higher proportion of genes was found to be upregulated in group Familiar compared to Novel.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies that compared gene expression in perirhinal cortices of rats exposed to either novel or familiar 3D objects or 2D images found increases in protein levels upon neuronal activation in response to the novel compared to the familiar stimulus [10], [11], [12], [13], [14], [37], [38]. Intriguingly, when the transcriptomes of groups Novel and Familiar were compared, a higher proportion of genes was found to be upregulated in group Familiar compared to Novel.…”
Section: Discussionmentioning
confidence: 83%
“…CaMKKa KO mice have deficits in contextual fear LTM as well as conditioninginduced CaMKIV activation, CREB phosphorylation, and transcription of the brain-derived neurotrophic factor (BDNF) gene (Blaeser et al 2006;Mizuno et al 2006). Furthermore, pharmacological inhibition of CaMKKa/b impairs CaMKIa activation as well as object recognition LTM (Tinsley et al 2012). Block of CaMKKa/b also impairs synthesis of plasticity-related proteins after strong LTP induction that is thought to contribute to LTM formation (Redondo et al 2010).…”
Section: Cam Kinase Cascadementioning
confidence: 99%
“…Recognition memory impairments are produced by infusing into perirhinal cortex inhibitors of these enzymes so as to interfere with consolidation mechanisms. Infusion of an inhibitor of CamK kinase (CamKK) immediately post-acquisition but not 20 min after acquisition impaired object recognition memory (Tinsley et al, 2012). Thus CamKK is important for perirhinal consolidation mechanisms necessary for recognition memory within the first 20–30 min after acquisition.…”
Section: Object Recognition Memory: Drug Actions On Consolidationmentioning
confidence: 99%
“…Accordingly, if memory rather than perceptual deficits are sought it is important that the stimuli used in recognition memory tasks are readily perceptually discriminable. The many studies that have found deficits in recognition memory tasks using two objects with many distinguishable features suggests that the impairment is not readily explained as solely a perceptual failure (Barker et al, 2006a,b, 2007; Seoane, Massey, Keen, Bashir, & Brown, 2009, 2011, 2012; Tinsley et al 2009, 2011; Tinsley, Narduzzo, Brown, & Warburton, 2012). At the same time, studies in monkeys and rats have established that perirhinal lesions produce perceptual impairment if stimuli have overlapping features so that discrimination requires judgement of differences in stimulus conjunctions within an object and cannot easily be based on single feature differences between objects (Bartko et al, 2007a,b; Buckley, Booth, Rolls, & Gaffan., 2001; Bussey et al, 2002).…”
Section: Introductionmentioning
confidence: 99%